Analisis Keputusan Petani Menggunakan Pupuk Organik, Anorganik, dan Campuran Pada Usahatani Padi Sawah - Hasugian, Hardy; Kesuma, Sinar I Indra; Wibowo, Rulianda Purnomo (Universitas Galuh, 2025)
The scarcity of chemical fertilizers has led to an increase in fertilizer prices, so farmers are reluctant to use chemical fertilizers that are too expensive and switch to using organic fertilizers. The application of organic fertilizers is not as a substitute for inorganic fertilizers but as a complement, so that in conventional cultivation organic fertilizers should be used in an integrated manner with inorganic fertilizers to increase soil and plant productivity in a sustainable manner. The purpose of this study was to analyze the decision of the use of organic fertilizers, inorganic fertilizers, and mixtures in rice farming in Sei Bamban Kiri village, Sei Bamban district, Serdang Bedagai Regency. Determination of the research area is done purposively. The sample size is determined by the Slovin method, which is as many as 90 respondents. The method of analysis to analyze the decision of farmers in purchasing the type of fertilizer used is multinomial logistic regression. The results showed that the age and number of family members have a big role in improving the decision of farmers to use fully organic fertilizer. Education Level, age, land area, and having a side job have a big influence in improving farmers ' decisions to use inorganic fertilizers. The level of Education, number of family members, land area, and care for the ecosystem have a big role in improving farmers ' decisions to use mixed fertilizers.